Impact of Different Evaluation Methods for Diagnostic Tasks in Panoramic Radiography - Brasil, Danieli M.; Gaêta-Araujo, Hugo; Almeida, Solange M.; Angeli, João P. B.; Roque-Torres, Gina D. (Odovtos - International Journal of Dental Sciences, 2021)
The aim of this study was to evaluate the observers’ diagnostic performance in panoramic radiography using monitor, tablet, X-ray image view box, and against window daylight as a visualization method in different diagnostic tasks. Thirty panoramic radiography were assessed by three calibrated observers for each visualization method, in standardized light conditions, concerning dental caries, widened periodontal ligament space, and periapical bone defects from the four first molars; mucosal thickening and retention cysts in maxillary sinus; and stylo-hyoid ligament calcification and atheroma. A five-point confidence scale was used. The standard-reference was performed by two experienced observers. Diagnostic values using window light were significantly lower for caries and periapical bone defect and retention cyst, stylo-hyoid ligament calcification detection (p<0.05). For atheroma detection, X-ray image view box, tablet, and widow light had lower accuracy than the evaluation on the monitor (p<0.05). Observer’s diagnostic performances are worsened using window light as an evaluation method for panoramic radiography for dental, sinus, and calcification disorders, while the monitor was the most reliable method.